2010
DOI: 10.3109/15622970902718774
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dopamine on intracellular sodium: A common pathway for pharmacological mechanism of action in bipolar illness

Abstract: A similar exercise has previously suggested that lithium and effective anticonvulsants reduce sodium influx in an activity-dependent manner. The current review suggests that antipsychotic medications may have a similar effect by a different mechanism. The role of ion dysregulation in the genesis of mania in bipolar illness needs to continue to be examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…In particular, excess dietary sodium has been linked to elevations in blood pressure (BP) (18). Previous studies have shown that high levels of tissue sodium are associated with a variety of conditions ranging from elevated BP to brain tumors, stroke, and bipolar disorder (8,9,28,36,42,47,51,55). Recent research has highlighted the importance of cerebral spinal fluid (CSF) sodium in regulating sympathetic activity in experimental rat (26,37,39) and mouse models (40,53).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, excess dietary sodium has been linked to elevations in blood pressure (BP) (18). Previous studies have shown that high levels of tissue sodium are associated with a variety of conditions ranging from elevated BP to brain tumors, stroke, and bipolar disorder (8,9,28,36,42,47,51,55). Recent research has highlighted the importance of cerebral spinal fluid (CSF) sodium in regulating sympathetic activity in experimental rat (26,37,39) and mouse models (40,53).…”
Section: Introductionmentioning
confidence: 99%
“…We believe that the different by an activity-dependent inhibition of Na ϩ channels (El-Mallakh and Huff 2001). Mood stabilizing antipsychotics may also have an effect of reducing intracellular sodium (Roberts et al 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Enzymatic activity is highly dependent on magnesium and lithium directly inhibits GSK-3β by acting as a competitive inhibitor of magnesium; magnesium being a cofactor for ATP in GSK-3β activation (Fig. 4) (Ryves and Harwood 2001). Thus, GSK-3β inhibition by lithium protects/rescues the brain from apoptotic cell death; and neural dysfunction results from the failure to completely inhibit GSK-3β (Grimes and Jope 2001a).…”
Section: Lithiummentioning
confidence: 99%
“…An increase in intracellular sodium concentration mediated by dopaminergic pathways is a characteristic of bipolar disorder and lithium normalizes this increase (Roberts et al 2009). Studies show that combined estrogen and lithium alter serotonin and dopamine metabolites.…”
Section: Estrogen and Lithium; Or Lithium As A Selective Estrogen-mementioning
confidence: 99%